Causative Factors of Increasing Prescription Drug Abuse based on Transcultural Nursing Theory - Ah Yusuf1 , Muhammad Tarmizi2 , Makhfudli3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Prescription drugs abuse in society is becoming a serious problem in the world. This case is caused by avariety of factors both internal and external, especially cultural factors. Various efforts have been done toreduce this problem but have not showed optimal results. This research was conducted to analyze the factorsrelated to drug abuse in the society based on transcultural nursing theory. This research was conducted intwo villages in the South Kalimantan Province of Indonesia, using a correlational research design with across-sectional approach. A total of 125 respondents suspected of abusing prescription drugs, were examinedusing a questionnaire. The sample selection using simple random sampling technique. Prescription drugabuse behavior was measured using a screening test CAGE-AID. The collected data was tested using alogistic regression test. Religious and philosophical factors (p = 0.035); kinship and social factors (p =0.038); cultural and lifestyle factors (p = 0.038); political and legal factors (p = 0.031); and economicfactors (p = 0.015) have a significant relationship with the behavior of drug abuse in the society. Meanwhile,technological factors (p = 0.092) and education (0.062) have no relationship with these behaviors. Easyaccess to drugs and the acceptance of this problem in the society have led to the higher cases of prescriptiondrugs abuse. Counseling related to the use of prescription drugs as well as an increase in rehabilitation andreligious programs need to be improved to prevent further abuse.